2023
DOI: 10.3389/fpsyt.2023.1124796
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacogenetics of the new-generation antipsychotics – A scoping review focused on patients with severe psychiatric disorders

Abstract: Exploring the possible correlations between gene variations and the clinical effects of the new-generation antipsychotics is considered essential in the framework of personalized medicine. It is expected that pharmacogenetic data will be useful for increasing the treatment efficacy, tolerability, therapeutic adherence, functional recovery, and quality of life in patients with severe psychiatric disorders (SPD). This scoping review investigated the available evidence about the pharmacokinetics, pharmacodynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…Differences in pharmacokinetics and pharmacodynamics of brexpiprazole due to possible impact of gene variability requires further exploration. Unfortunately, however, data on the impact of genetic variations on brexpiprazole pharmacodynamics and tolerability are still limited 37 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in pharmacokinetics and pharmacodynamics of brexpiprazole due to possible impact of gene variability requires further exploration. Unfortunately, however, data on the impact of genetic variations on brexpiprazole pharmacodynamics and tolerability are still limited 37 …”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, however, data on the impact of genetic variations on brexpiprazole pharmacodynamics and tolerability are still limited. 37 Despite their widespread use, attention to potential tolerability issues other than akathisia is important when considering using antipsychotic medication in patients with MDD. 38 Extrapyramidal symptoms, metabolic syndrome effects, increased prolactin levels, and subjective negative experiences such as insomnia are particularly important to consider.…”
Section: Pcn Psychiatry Andmentioning
confidence: 99%
“…Currently, antipsychotic medications are the primary treatment modality for schizophrenia. Certain clinical studies indicate that the combination of antipsychotic drugs with nonsteroidal anti-inflammatory drugs and anti-inflammatory agents can ameliorate symptoms in individuals with schizophrenia ( 39 ). Over time, research has revealed intricate connections between the immune system, inflammation, and alterations in mood, cognition, and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Articles were excluded from this revision for the following reasons: (1) not drug of interest (not antipsychotics); (2) other areas of research (Alzheimer disease, depression, implementation of informatic tools, etc. ); (3) not original new data (reviews of publications); (4) case-report studies; (5) studies with exclusive pharmacokinetic design and outcomes; (6) studies with not reported response phenotype. A total of 269 relevant papers were identified that reported original pharmacogenetic or pharmacogenomic results on a variety of antipsychotic response phenotypes (influence of genetic variants on treatment response, adverse reactions and/or drug clearance).…”
Section: Literature Reviewmentioning
confidence: 99%
“…At present, the implementation of pharmacogenetic interventions in psychiatric settings is very limited, and further proof of their clinical utility is required. Pharmacogenomic research conducted in the last decade has advanced our knowledge on the mechanism of action of antipsychotic drugs by confirming the therapeutic value of known targets [ 2 , 6 ]. Further research into genomic and epigenomic factors contributing to response may help to improve the accuracy and clinical applicability of genetic information in psychiatry.…”
Section: Introductionmentioning
confidence: 99%